EFFECT OF LAYER THICKNESS ON PROPERTIES OF SLA PARTS WITH DIFFERENT SHAPES - WANG FengMei; GAO Fei; WU XiangWei; ZHAO JiaXu; LI PengFei; XU WeiDong; WANG ShaoHua (Jixie qiangdu, 2022)
Somoss Imagine 8000 photosensitive resin was used to prepare test parts with various shapes, such as plane, bridge, round hole, nut, etc., by stereo lithography appearance. The surface accuracy, dimensional accuracy, tensile properties and printing time of different shapes under different layer thickness were studied. The results show that the surface accuracy of the test piece is the worst when the thickness is 0.06 mm, and the best when the thickness is 0.08 mm. The dimensional accuracy of the upper support surface of the test piece decreases with the increase of the thickness of the layer. If the thickness is too small, the “Z” axis surplus phenomenon appears, which leads to the increase of the dimensional accuracy in the height direction. However, the thickness of the layer has little effect on the dimensional accuracy in horizontal direction. The dimensional accuracy of the bridge, the fine gap, the wall thickness and the nut were the worst when the layer thickness was 0.06 mm.The dimensional accuracy is better when the layer thickness is 0.1 mm and 0.08 mm.When the thickness increases from 0.08 mm to 0.1 mm, the tensile strength decreases from 48.98 MPa to 46.62 MPa, which decreases by 4.8%.Elongation decreases from 2.4% to 1.6%, all less than 5%, indicating that the strength of the material can be improved by appropriately reducing the thickness of the layer. The layer thickness is inversely proportional to the printing time. When the layer thickness increases from 0.06 mm to 0.1 mm, the printing time is shortened by 67% and the printing efficiency is improved.